Community's knowledge, perceptions and preventive practices on Onchocerciasis in Jimma zone, Ethiopia, formative mixed study. - Daba Abdissa; Yohannes Kebede; Morankar Sudhakar; Gelila Abraham; Gebeyehu Bulcha; Teshome Shiferaw; Nimona Berhanu; Firanbon Teshome; Hirpa Miecha; Zewdie Birhanu (Public Library of Science (PLoS), 2024)
Background In Ethiopia, Onchocerciasis is a prevalent neglected tropical disease, currently targeted for elimination with mass drug administration and community behavioral changes towards sustained control and eventual elimination. This study aimed to elucidate the awareness, perceptions and practices of endemic communities in Jimma Zone, Ethiopia. Methods and materials Community-based cross-sectional study triangulated with qualitative method was conducted from October-November, 2021. A multistage sampling was employed and data were collected using a pre-tested interviewer-administered structured questionnaire. Logistic regression was used to identify the predictors of comprehensive knowledge and preventive practice. Adjusted odds ratios were calculated at 95% confidence interval (CI) and considered significant with a p-value of <0.05. Kruskal-Whallis and Mann-whitney tests were used to compare median risk perception score by socio-demographic factors. Qualitative data were collected through focus group discussions and key informant interviews and transcribed verbatim. Then the data were coded, categorized, and themes were developed. Result The overall prevalence of adequate comprehensive knowledge was 48.8% (95% CI: 44.9, 52.3), high risk perception was 18.7% (95%CI15.9, 21.4) and preventive practice was 46.9%(95%CI:(43.3,50.4). High risk perception[AOR = 1.95 95%CI: (1.32, 2.89] was statistically significant with comprehensive knowledge, likewise knowledge of mode of transmission [AOR = 2.64 95% CI: (1.44, 4.85)], knowledge of consequences [AOR = 2.12 95%CI: (1.21, 3.72)] and knowledge of preventive measures [AOR = 15.65,95%CI:(10.1, 24.2)] were statistically significant with preventive practice. The median risk perception was varied significantly between the groups by educational status, study district and age category. Qualitative evidence showed that there were great community knowledge gap about the disease. Conclusion Community knowledge, perceptions, and practices are unacceptably low. Risk perception was significantly associated with comprehensive knowledge, likewise knowledge of mode of transmission, consequences and preventive measures were significantly associated with preventive practice. This implies knowledge is a key component of effective prevention strategies as it is a necessary condition for the behavior change.